Verbal Art in the Heat of the Sinai: Harwerre’s Inscription (IS 90) - Stauder, Andréas (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
Study of Harwerre’s inscription at Serabit el-Khadim (IS 90; year 6 of Amenemhat III). Part 1 offers a philological discussion and new translation of this difficult text. Part 2 shows how the textual composition is patterned throughout on all hierarchical levels. (A proposal for calibration in prosodically patterned Middle Kingdom texts is outlined, differing from both Fechtian “metrics” and Fosterian “thought couplets.”) The patterning extends to deep rhythmical levels, supporting the hypothesis that the text could have been recited on occasions. The overall form of the composition, at once bipartite and concentric, foregrounds the turn to success brought about by the king’s “might” ( bȝw ). Superimposed on this, a concentric framing, rhythmical patterning, and phonetic echoes concur in celebrating “Hathor” ( ḥwt-ḥr ) as lady of the “beautiful skin” ( ỉnm nfr ). Part 3 relates the textual composition to its contexts: the stela on which it is inscribed, the place where that stela stands, and the time of Amenemhat III. This is tightly integrated with the other pictorial and written elements on the stela whose two faces mediate between the powers in the sanctuary (eastern face) and the incoming visitor (western face). On the western face, the turn to success through the king is set in the exact middle lines 13–14 of the 26-line long textual inscription, meeting the incoming visitor at roughly eye’s height. Echoes of Harwerre’s text in neighboring inscriptions of the immediately following years attest to the local reception of an out-of-the-ordinary text and monument. The product of a composer versed in the patterns of contemporary poetry, the text is a token of a productive reception of such during the reign of Amenemhat III.